New clues to understand gastroschisis. Embryology, pathogenesis and epidemiology (Colombia Medica, 2021)
Gastroschisis is a congenital structural defect of the abdominal wall, most often to the right of the umbilicus, through which the abdominal viscera protrude. For a long time, its developmental, etiological, and epidemiological aspects have been a hot topic of controversy. However, recent findings suggest the involving of genetic and chromosomal alterations and the existence of a stress-inducing pathogenetic pathway, in which risk factors such as demographic and environmental ones can converge.To expand the frontier of knowledge about a malformation that has shown a growing global prevalence, we have conducted a review of the medical literature that gathers information on the embryonic development of the ventral body wall, the primitive intestine and the ring-umbilical cord complex, as well as on the theories about its origin, pathogenesis and recent epidemiological evidence, for which we consulted bibliographic databases and standard search engines.